Risiko Usaha dan Strategi Pengembangan Agroindustri Olahan Berbahan Dasar Ikan “UD Diana Indah” di Desa Gelung Kecamatan Panarukan Kabupaten situbondo - Primasari Puspitaningrum; Ati Kusmiati (UNEJ e-Proceeding, 2018)
Fisheries sub-sector is one of the sub-sectors that has a strategic role innational development because the potential of Indonesia's natural resources as the largestmaritime country with fishery resources that the number is relatively large and scatteredalmost throughout the Indoneisa region. The research is aimed to know 1) Income of agroindustry "UD Diana Indah" in harvest season and famine season, 2) the risk of agroindustry "UD Diana Indah" in harvest season and famine, 3) development strategyon fish-based agroindustry of "UD Diana Indah". The research method used descriptiveand analytical. The sampling method was chosen by non probability sampling techniqueof purposive sampling. Data analysis used income analysis, risk analysis and Force FieldAnalysis (FFA). The results showed 1) Average monthly income that received by ―UD.Diana Indah", in its activities to produce fish rengginang in harvest season of 2017which is Rp. 4.852.264 and famine Rp. 1.347.819. Fish cracker products have an averagemonthly income in 2017 harvest season of Rp. 1.256.049 and famine season of Rp.175.611. 2) The Production process of fish rengginang both in harvest-famine season andfish cracker in harvest season has a very small risk level with value of coefficient variation< 0.5 respectively of 0.45, 0,22. and 0,44 and the lowerbound of profit or value of L >0,respectively of Rp. 525.098, Rp. 556.051 and Rp. 29.218 which means in everyproduction process of fish rengginang, no chance of losing from production process. Theproduction of fish crackers during the famine season has a greater risk level with thevalue of coefficient variation > 0.5 that is equal to 0,79 and lowerbound of profit < 0 is Rp– 517.157 which means that the production process of fish crackers during the famineseason has a chance in losing from every production process 3) focus strategy which isdetermined by agroindustry of "UD. Diana Indah" by partnering with several fishermenwho located in Situbondo and optimally use the government support in increasingproduction and productivity in terms of quality and quantity of fish rengginang and fishcrackers.